PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN CITRA MERK TERHADAP KEPUTUSAN PEMBELIAN PRODUK HANDPHONE MEREK APPLE - Aldino Jacky Royani; Wiyadi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of product quality, price, promotion and brand image on purchasing decisions for Apple brand mobile phone products. This study uses a quantitative approach with a survey method. The research sample was 100 respondents using purposive sampling method with the following criteria: (1) Consumers and users of apple brand smarphone, (2) Aged 18-35, (3) People residing in Solo Raya. The data analysis used is instrument test, classical assumption test, multiple linear regression test, hypothesis test, and determination coefficient test. The results showed that product quality, price, promotion, and brand image partially had a significant positive effect on purchasing decisions.